JAVANESE GAMELAN IN THE PERSPECTIVE OF SAYYED HOSSEIN NASR - Nauval, Ach. Nauval Afandi Enhas; Khudori, Achmad Khudori Soleh; Hasan, Nor Hasan (Islamuna: Jurnal Studi Islam, 2025)
ABSTRACT This study explores the potential of gamelan music art in the context of being a spiritual medium, through the perspective of the philosophy of art, especially the thoughts of Sayyed Hossein Nasr. The purpose of this study is to reveal the position of Javanese Gamelan from the perspective of Islamic art from Sayyed Hossein Nasr, the spiritual and philosophical values ​​in Javanese Gamelan, and the relationship between traditional art and Islamic values. This study is a library research by collecting data from various literature sources. This study concludes, (1) in the classification of Sayyed Hossein Nasr's art, gamelan music art is included in the category of traditional art because gamelan has spiritual value and is indirectly related to religion. (2) Gamelan has spiritual value because it is used as a tool to perform rituals to get closer to God. (3) Art in Islamic civilization is formed on the basis of awareness of the oneness of God so that gamelan players and listeners reach a transcendental state, so that they feel they are at a higher stage of consciousness where their souls will feel close to their God. This research contributes to the discourse of Islamization of knowledge by offering an alternative paradigm in understanding art. In addition to being entertainment, Gamelan can be used as an object of Islamization of knowledge by being interpreted religiously symbolic and studied philosophically within the framework of monotheism. ABSTRAK Kajian ini menggali potensi seni musik gamelan dalam konteks sebagai sarana spiritual, melalui perspektif filosofi seni, khususnya pemikiran Sayyed Hossein Nasr. Tujuan penelitian ini adalah mengungkap posisi Gamelan Jawa perspektif seni Islam Sayyed Hossein Nasr, nilia-nilai spiritual dan filosofis dalam Gamelan Jawa, serta hubungan seni tradisional dengan nilai-nilai Islam. Penelitian ini merupakan penelitian kepustakaan atau library research dengan mengumpulkan data dari berbagai sumber literatur. Penelitian ini menyimpulkan, (1) dalam klasifikasi seni Sayyed Hossein Nasr, seni musik gamelan termasuk dalam kategori seni tradisional karena gamelan memiliki nilai spiritual dan secara tidak langsung berhubungan dengan agama. (2) Gamelan memiliki nilai spiritual karena digunakan sebagai alat untuk melakukan ritual untuk mendekatkan diri kepada Tuhan. (3) Seni dalam peradaban Islam dibentuk atas dasar kesadaran akan keesaan Tuhan sehingga membuat pemain gamelan dan pendengar mencapai keadaan transendental, sehingga mereka merasakan berada di tahap kesadaran yang lebih tinggi yang mana jiwa mereka akan merasa dekat dengan Tuhannya. Penelitian ini berkontribusi terhadap wacana Islamisasi ilmu dengan menawarkan paradigma alternatif dalam memahami seni. Selain sebagai hiburan, Gamelan bisa dijadikan sebagai objek Islamisasi ilmu dengan dimaknai secara religius simbolik dan dikaji secara filosofis dalam kerangka tauhid.